The Interface between Inflammation and Coagulation in Cardiovascular Disease. (19th February 2012) - Demetz, Gabriele; Ott, Ilka
Abstract : The intimate connection between coagulation and inflammation in the pathogenesis of vascular disease has moved more and more into focus of clinical research. This paper focuses on the essential components of this interplay in the settings of cardiovascular disease and acute coronary syndrome. Tissue factor, the main initiator of the extrinsic coagulation pathway, plays a central role via causing a proinflammatory response through activation of coagulation factors and thereby initiating coagulation and downstream cellular signalling pathways. Regarding activated clotting factors II, X, and VII, protease-activated receptors provide the molecular link between coagulation and inflammation. Hereby, PAR-1 displays deleterious as well as beneficial properties. Unravelling these interrelations may help developing new strategies to ameliorate the detrimental reciprocal aggravation of inflammation and coagulation.